Recent Advances in Surface and Coatings Technology (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Development of new surfaces and coatings has resulted in scientific and technological progress. Coatings technology offers the possibility of producing advanced surface with tailored physicochemical and biological properties to meet requirements for food, biomedical, and environmental applications. This e-book gathers recently published papers that have attracted considerable attention and consideration, providing updates on this research topic. Specifically, this book collects new information on designed surfaces, coatings, and materials based on metals, polymers, ceramics, and composites. Some research describes the techniques for the preparation and characterization of gel, functional surfaces, and coatings, and their potential application in drug delivery or films for food preservation. Other studies outline different surface preparation processes or novel techniques for modifying the surface features for load-bearing implant applications. One paper focuses on the synthesis of stimuli-responsive hydrogels for new perspectives such as active coatings for cotton-cellulose fabric. A review is devoted to probiotic microencapsulation technology. The collection delivers scientific findings to both academic and industrial readers.